Tradisi Tedhak Siten Terkandung Konsep Self Efficacy Masyarakat Jawa - Ana Musdalifah; Taufik Akbar Rizky Yunanto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The tradition of tedhak siten is still widely believed by Javanese people to this day. In the process of tedhak siten there are 6 stages that must be passed by a child, one of which is a stage in confinement. At parents this stage raises the perception of self-efficacy after the child chooses the items in the cage, it is believed that the items selected are a process of description that will occur in children as adults. The purpose of writing this article is in addition to being interested in the writer wants to understand more scientifically the relationship between culture tedhak siten with psychological aspects, also interested in the relationship between career and family perception. Data was collected through literary source techniques for collecting various related journals and articles. The results of writing this article indicate that the process of tedhak siten ceremony contains values, the goodness that comes from parents for children is able to achieve their ideals, which are closely related to psychological theory, namely self efficacy.